Pengaruh Stres dan Kepuasan Kerja terhadap Kinerja Perawat Rumah Sakit Ibu dan Anak Eria Bunda Pekanbaru - Chairizal, Tedy Novianto; Ningsih, Dewita Suryati; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research was conducted on Ibu dan Anak Hospital in Pekanbaru that aims to determine the influences of Sress and Work Satisfaction either simultaneously or partially on Performance of Nurses in Ibu dan Anak Hospital in Pekanbaru. The methodology in this study is: Stress and job satisfaction significant influence on Nurses performance in Ibu dan Anak Hospital in Pekanbaru and the dominant factor affecting the performance of Nurses is Job Statisfaction. While the population in this study is the Nurses on Ibu dan Anak Hospital which amounted to 69 people, with a total sample of 96 respondents. Multiple Linear Regression Analysis method by using SPSS version 17. Simultaneous regression (F test) showed that the independent variables studied (Sress and Job Satisfaction) together (simultaneously) have a significant influence on the dependent variable (Nurse performance). The magnitude of the effect that (R2) by the two independent variables together against the dependent variable, while the remaining is influenced by other variables not examined in this study. The results of the testing that has been done, the partial regression test (t test) showed that each of the independent variables studied (Stress and Job Satisfaction) has a significant effect on Ibu dan Anak Hospital the dependent variable (Nurse performance). Dominant variables affecting nurse performance in ibu dan anak Hospital in Pekanbaru is Sress where the value of t-counted highest compared with other independent variables.Keywords: Stress, Job Satisfaction and Nurse Performance